AHP based technical, economic and environmental impact analysis with optimal DG placement in radial distribution network - Tanwar, Surender Singh; Prajapat, Ganesh Prasad; Rathod, Ravindra; Bansal, Sanjay Kumar; Sisodia, Sukhlal (Institute of Advanced Engineering and Science, 2024)
This manuscript considers multi-criteria based multi-objective approach with technical, economic and environmental indices (TEE) for optimal placement and sizing of distributed generation (DG) units in the distribution network. Technical criteria include indices of active energy losses, voltage deviation; whereas economic criteria include the index of cost of DG installation, and environmental index considers the various greenhouse gas (GHG) emissions from generating unit’s and biomass DG. Combined sensitivity analysis is applied for sorting the candidate nodes for DG placement and reducing the search space. Multi-criteria decision-making among TEE factors are addressed using a scientific approach named Analytic Hierarchy process (AHP) approach. The impact of prioritized solutions is analyzed in terms of three scenarios formed using AHP in the form of TEE criterion. The developed formulation is tested on IEEE 33-bus bus radial distribution system and is solved using hybrid optimization approach (hybrid GA-PSO) and AHP based scenarios performed better than base case scenario (non-prioritized scenario).